Parabacteroides distasonis attenuates toll‐like receptor 4 signaling and Akt activation and blocks colon tumor formation in high‐fat diet‐fed azoxymethane‐treated mice - Koh, Gar Yee; Kane, Anne; Lee, Kyongbum; Xu, Qiaobing; Wu, Xian; Roper, Jatin; Mason, Joel B.; Crott, Jimmy W. (International journal of cancer, 2018)
Gut dysbiosis may play an etiological role in colorectal tumorigenesis. We previously observed that the abundance of Parabacteroides distasonis (Pd) in stool was inversely associated with intestinal tumor burden and IL‐1β concentrations in mice. Here, we assessed the anti‐inflammatory capacity of Pd membrane fraction (PdMb) in colon cancer cell lines. In addition, we tested whether Pd could suppress colon tumorigenesis in mice. Six‐week‐old male A/J mice were fed a low‐fat (LF) diet, high‐fat (HF) diet or HF+ whole freeze‐dried Pd (HF + Pd, 0.04% wt/wt) for 24 weeks. After 1 week on diet, mice received 4 weekly injections of azoxymethane. PdMb robustly suppressed the production of pro‐inflammatory cytokines and lowered the abundance of MyD88 and pAkt (ser473) induced by E. coli lipopolysaccharide in colon cancer cell lines. Moreover, PdMb induced apoptosis in colon cancer cell lines and blocked TLR4 activation in a reporter line. Colon tumors were observed in 0% of LF (0 of 19), 25% of HF (5 of 20) and 0% of HF + Pd mice (0 of 20) (p = 0.005). The latter group also displayed a lower abundance of MyD88 and pAkt (ser473) in colonic mucosa than HF mice. Taken together, these data suggest that Pd has anti‐inflammatory and anti‐cancer properties that are likely mediated by the suppression of TLR4 and Akt signaling, as well as promotion of apoptosis. Further work is needed to confirm these findings in additional models and fully elaborate the mechanism of action. What's new? Inflammation constitutes a major mechanistic link between obesity and tumor risk. Gut microbial dysbiosis may also play an etiological role in colorectal tumorigenesis. The abundance of commensal Gram‐negative anaerobe Parabacteroides distasonis (Pd) in stool was previously observed to be inversely associated with intestinal tumor burden and IL‐1β in mice. Here, in an obesity‐driven model of colorectal cancer, Pd was shown to have anti‐inflammatory and anti‐cancer properties that are likely mediated by the suppression of TLR4 and Akt signaling, and promotion of apoptosis. The findings suggest that administering specific protective bacterial species could have utility in the prevention of colorectal tumorigenesis in at‐risk populations.